Design and development of a hybrid machine combining rapid prototyping and CNC milling operation - Amanullah, A.N.M.; Murshiduzzaman, Sheikh; Saleh, Tanveer; Khan, Md. Raisuddin (Elsevier, 2017)
Nowadays, two most important processes, namely rapid prototyping (RP) and CNC machining are being used to produce prototypes. CNC machining (subtractive method) is relatively more precise and accurate, but it is tough to create stuffs with complex features. RP (additive method), by contrast, is able to form parts with sophisticated features, that consents materials to be utilized more efficiently. But its entire automation emanates with conciliations in the qualities of material and geometry. Combining both subtractive and additive process on a single platform has significant advantages. However, this has several challenges such as control system integration and maintaining accuracy of alignment during the change over process. This research attempts to assimilate both of these processes and propose a new design of hybrid machine with the purpose of overcoming the drawbacks related with different control panel and misalignment issues. Fused deposition modeling (FDM) is considered as the RP process in this study. A CNC cutting spindle and an FDM heat extruder has been designed to be placed respectively in front of a rotary stage which will be used to overcome the misalignment with the help of IR sensors. The proposed design allows CNC milling and FDM process in a single setup thus attaining the benefit of decreasing expenses for additional actuators.